2015
DOI: 10.22621/cfn.v129i2.1701
|View full text |Cite
|
Sign up to set email alerts
|

Anti-predator defenses of Brown Bullheads (<em>Ameiurus nebulosus</em>) and interactions with Snapping Turtles (<em>Chelydra serpentina</em>)

Abstract: . 2015. Anti-predator defenses of Brown Bullheads (Ameiurus nebulosus) and interactions with Snapping Turtles (Chelydra serpentina). Canadian Field-Naturalist 129(2): 189-193.Ictalurid catfishes have sharp spines on their dorsal and pectoral fins that can be hazardous to predators. The pectoral spines may lock in an abducted position, effectively increasing body size and preventing ingestion by gape-limited predators. Further, sharp spines may injure predators or increase prey handling time, affording catfish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…However, this species, due to its biological and physiological features, spread almost throughout Europe and became a problem for many aquatic ecosystems of areas it invaded (Holčík, 1991). Possible reasons for the success of this invasion of the brown bullhead populations are their potential to survive in sediment during short periods of drought, a high degree of parental care (Blumer, 1985), and also a lack of natural enemies due their ability to erect dorsal and pectoral spines as a defense against predators (Scott and Crossman, 1973;Kornijów, 2001;Moldowan et al, 2015), and their tolerance of a variety of environmental stressors such as contaminants (Pyron et al, 2001) and very low oxygen concentration (less than 0.2 mg L -1 ). According to many sources cited by Rutkayova et al (2013), the brown bullhead is found in many European countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, this species, due to its biological and physiological features, spread almost throughout Europe and became a problem for many aquatic ecosystems of areas it invaded (Holčík, 1991). Possible reasons for the success of this invasion of the brown bullhead populations are their potential to survive in sediment during short periods of drought, a high degree of parental care (Blumer, 1985), and also a lack of natural enemies due their ability to erect dorsal and pectoral spines as a defense against predators (Scott and Crossman, 1973;Kornijów, 2001;Moldowan et al, 2015), and their tolerance of a variety of environmental stressors such as contaminants (Pyron et al, 2001) and very low oxygen concentration (less than 0.2 mg L -1 ). According to many sources cited by Rutkayova et al (2013), the brown bullhead is found in many European countries.…”
Section: Introductionmentioning
confidence: 99%
“…A presença de nadadeiras desenvolvidas pode, de forma semelhante aos membros dos lagartos, dificultar ou impossibilitar a ingestão de peixes iniciando-se pela cauda (e.g. Moldowan et al, 2015). No entanto, dos peixes predados para os quais a família foi identificada, 91,25 % pertencem às famílias Synbranchidae, Gymnotidae, Sternopygidae e Hypopomidae, nas quais as nadadeiras estão ausentes ou são rudimentares (Nelson et al, 2016).…”
Section: Discussionunclassified